Drivers and Barriers to the Adoption of Telemedicine among Persons with Chronic Health Conditions in Ghana - Hyde-Quartey, Linda; Zhang, Xinjie; Ahoto, Ahotovi Thomas (International Journal of Management Innovation Systems, 2024)
Telemedicine has been established as a major technological breakthrough in health delivery as it is expected to influence the growth in virtual health delivery procedures with continuous advancements in technology and improved internet connectivity. Per the increasing cases of chronic diseases in the global population, telemedicine can ease routine treatment and reduce expenditure on treatment. With all the strong research support for the adoption of telemedicine, developing countries in Africa are yet to benefit from telemedicine due to technology and other gaps. The study investigates the adoption of telemedicine for treating chronic diseases in Ghana. A quantitative research method was adopted using a linear hierarchical regression model to measure relationships between variables of the behavioral change model (health belief model) concerning telemedicine adoption. The study results show that perceived benefits, perceived severity and perceived self-efficacy have positive effects on the adoption of telemedicine. However, perceived barriers and cues to action negatively affect telemedicine adoption. Cues to action again have negative effects on perceived benefit and perceived self-efficacy. The researchers recommended that efforts should be made to reduce barriers to telemedicine adoption by improving internet connectivity, reducing language barriers between medical staff and patients and providing the right information about telemedicine procedures to patients.